Knowledge, Understanding, and Application of Industrial Training Towards The Students of Catering Study Program - Adibah Aishah Md ahak; Abdul Rasid Abdul Razzaq; Syed Shikh Syed A. Kadir; Mohd Akmal Rohiat; Raden Mohd Farhan Helmy Raden Ismail; Abdul Wafi Abdul Rahman; Laila Sari Bahanin (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Industrial Training Course is essential and give the positive impact for the curriculum of bachelor’s degree program at Tun Hussein Onn University Malaysia (UTHM. This study aimed to look at knowledge, understanding and application of industrial training to catering students at the Faculty of Technical and Vocational Education, University of Tun Hussein Onn Malaysia (UTHM). This study is descriptive study that used a five -point Likert scale questionnaire as an instrument. A total of 66 final year students from the Vocational Catering program were used as the study sample. The collected data were analyzed using Statistical Package for the Social Science version 23.0 for Windows (SPSS). The results show that the level of knowledge, understanding and application of industrial training is high with a mean score 4.29. In addition, catering students also know that knowledge, understanding and application of industrial training were positive to enhance their academic performance and achievement in the program. The results of this study can serve as a guide for exposing students to the real work environment to be better prepared for the future.